CSI, crime scene investigation. The fourteenth season [videorecording (DVD)]. - Danson, Ted, 1947-; Eads, George, 1967-; Guilfoyle, Paul; Szmanda, Eric; Langham, Wallace; Shue, Elisabeth; Fox, Jorja (CBS, 2014)
In the fourteenth gripping season, from a serial slaughter and arson to mysterious disappearances and cannibal killings, lead investigator D.B. Russell uses science to shed light on the darkest crimes. With the help of blood-work expert Julie Finlay and veteran investigators Nick Stokes, Sara Sidle and Greg Sanders, the evidence never slips through the cracks.